Archetypes in ancient manuscripts and their significance and value in the kazakh spiritual ethno culture - Suiyerkul, Botagoz; Aidarbek, Karlygash; Kurmanali Chakyroglu, Altynshash; Aitmukhametova, Kuralay; Madina, Duisenbekova (Opción, 2018)
The article considers origins of archetypes in Kypchak and Kazakh ethnic traditions. The most essential and unique archetypes such as Water, Earth, Air and Fire are discussed as eternal values for the Kazakh nation. The evidence of their importance and necessity for spiritual and cultural identity are found in the ancient Kazakh folk proverbs and sayings, as well as myths, beliefs and legends. To argue for their vitality the authors also quote manuscripts and sacred written texts. The meanings of archetypes are discussed in the lights of modern life.